The impact of government macroeconomic policies and elections on income smoothing in state-controlled commercial banks: Evidence from the MENA region - Pejman Peykani; Mostafa Sargolzaei; Mohammad Javad Mohagheghnia; Amir Takaloo; Mahsa Valimoradi (PLoS ONE, 2026)
In most of the economies of different countries in the world, banks play a very important role in economic stability. We know that if the banks are not managed correctly, this issue will have heavy economic, political and social consequences for the society of that country. If we can find the important factors in the correct and accurate management of banks in the economy of a country, it will help the sustainable economic growth of that economy. In this research, we seek to find out how political shareholders affect the management of banks. To achieve this goal, the financial information of commercial banks of ten countries in the Middle East and North Africa (MENA) region during the years 2015–2020 and also the Generalized Method of Moments (GMM) model have been used. After calculating the percentage of government shares in the investigated banks, we analyze income smoothing using loan loss provisions (LLPs). One of the factors that has been considered in this regard is the elections in these countries and income smoothing in election years has been compared with other years. The obtained results show that income smoothing is more in banks that have more government shareholders. Another noteworthy point is that the election factor has a significant impact on the management of banks.